Partisipasi Masyarakat Dalam Pengelolaan Hutan Adat Pasca Persetujuan Izin Perhutanan Sosial Di Desa Hukurila - Pelu, Sumiyati; Tjoa, Marthina; Imlabla, Wilma N (Jurnal Agrosilvopasture-Tech, 2024)
Forest management will fail if various parties do not participate. Community participation is one of the important things that must be considered in forest management. This study aims to determine the forms of community participation in customary forest management after the issuance of social forestry permits. The research method used in this research is descriptive qualitative method. To find out the forms of participation can be seen in the five forms of participation, namely the participation of ideas, energy, property, skills and proficiency, and social participation. The results of the study show that the forms of community participation in customary forest management after the approval of social forestry permits are in the form of thought participation, labor participation and social participation.